1997
DOI: 10.1046/j.1440-169x.1997.t01-1-00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of fibroblast growth factor signaling for regeneration of epiphyseal morphology in rabbit full‐thickness defects of articular cartilage

Abstract: The involvement of fibroblast growth factor-2 (FGF-2) during the repair process in rabbit full-thickness defects of articular cartilage was studied. Fibroblast growth factor-2 (50 pg/h) was administered for 2 weeks in a 5 mm defect of articular cartilage, which is large enough not to repair spontaneously. The administration of FGF-2 resulted in the regeneration of the articular cartilage and the subchondral bone within 8 weeks. In these defects, undifferentiated mesenchymal cells initiated chondrogenic differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 33 publications
3
94
0
1
Order By: Relevance
“…These findings are consistent with the idea that the articular cartilage and subchondral bone were regenerated by FGF-2 [17]. Thus, the histological findings are compatible with those of the mechanical analysis, indicating that the grafts transplanted with FGF-2 hydrogel were more stable than those in the control group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with the idea that the articular cartilage and subchondral bone were regenerated by FGF-2 [17]. Thus, the histological findings are compatible with those of the mechanical analysis, indicating that the grafts transplanted with FGF-2 hydrogel were more stable than those in the control group.…”
Section: Discussionsupporting
confidence: 90%
“…Weisser et al [27] reported that the treatment of chondrocyte cultures with FGF-2 had a stabilising effect on the differentiated state of the cells in vitro. Otsuka et al [17] reported that the articular cartilage Fig. 3a-c Histological evaluation of the junction between the graft and the host (Group I: defect filled with gelatin hydrogel including FGF-2, Group II: defect filled with gelatin hydrogel only, Group III: defect in which neither hydrogel nor FGF was used).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the bone defect was set at a diameter of 5.0 mm and depth of 6.0 mm, for which natural healing of cartilage is not expected, based on studies reported by Otsuka et al 17) and Reddi et al 18,19) . Regarding DDM, Urist et al demonstrated that organic substances account for about 20% of tooth dentin in weight; the principal component is type I collagen, similarly to bone, with a trace amount of bone morphogenetic protein (BMP) having osteoinduction ability 20) .…”
Section: Discussionmentioning
confidence: 99%
“…Under general anesthesia using intravenous pentobarbital (0.05 mg/kg) followed by isoflurane in oxygen gas anesthesia, through a medial parapatellar arthrotomy, a full-thickness osteochondral defect 5 mm in diameter and 2 mm deep was made by an electric-powered drill on the patellar groove of the bilateral distal femur. Previous studies have shown that such defects fail to repair spontaneously [40,41]. The tissue-engineered constructs using each scaffold-cushion-type or cylinder-type scaffold-were press-fit implanted into the defects after an eight week-cultivation in both treatment groups.…”
Section: Animal Model Experimentsmentioning
confidence: 99%